Studi Pengaruh Flame Straightening Terhadap Kekerasan Material High Strength Low Alloy (HSLA) - Nur Fitria Pujo Leksonowati; Salman Al Faris; Nurman Pamungkas (Politeknik Negeri Batam, 2021)
High strength low alloy (HSLA) steel has higher mechanical strength than steel in general but with easy weldability, in this study the material used is S690QL. Flame straightening is used to restore the distorted shape of the S690QL material due to the heating and cooling process during the fabrication process. The purpose of this study was to determine the hardness value of the S690QL material after going through the flame straightening process. Flame straightening process is carried out by line heating technique using temperature variations of 700 °C, 750 °C, and 800 °C for 45 minutes in each temperature variant. A nozzle with a diameter of 14 mm – 20 mm with a multi flame torch is used in the flame straightening process. As a step to reduce residual stress and stress relieving, Post Weld Heat Treatment (PWHT) with a holding time of 1 hour was carried out. The process is continued with water cooling to room temperature. Vickers hardness test is carried out by taking 9 sample points, 2 points on the base metal, and 7 points on the Heat Affected Zone area. Based on the test results, it is known that at temperatures of 700 and 750 there has been no phase change, so the highest hardness values ​​at these temperatures are 270 HVN and 295 HVN. While at a temperature of 800 °C, there was a phase change marked by the hardness value which increased to 379 HVN.